1987
DOI: 10.1007/bf00585064
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of the squid axon K+ channel by noxiustoxin: a toxin from the venom of the scorpionCentruroides noxius

Abstract: We have studied the selective effects of noxiustoxin (NTX), a fraction of the venom of the scorpion Centruroides noxius, on the K currents of perfused squid giant axons using the voltage-clamp technique. At concentrations below 1.5 microM, NTX blocked K currents in a voltage-independent manner, with little effect on their turning-on and turning-off kinetics. Above 1.5 microM, the block by NTX became voltage-dependent and could be partially removed by repetitive pulsing and strong depolarizations. Long repolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…ChTX was also compared with other known peptide inhibitors of K+ channels. A high level of similarity was detected between ChTX and noxiustoxin, a toxin from the venom of the scorpion Centuroides noxius that blocks the delayed rectifier K+ channel of the squid giant axon (20). The best alignment between ChTX and noxiustoxin (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…ChTX was also compared with other known peptide inhibitors of K+ channels. A high level of similarity was detected between ChTX and noxiustoxin, a toxin from the venom of the scorpion Centuroides noxius that blocks the delayed rectifier K+ channel of the squid giant axon (20). The best alignment between ChTX and noxiustoxin (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…However, two other compounds, TBA and NTX did inhibit the current. NTX has been shown to inhibit the maxi Ca2+-activated K + channel in membranes derived from transverse tubules of skeletal muscle incorporated into planar lipid bilayers with a Kd of 450 nM (Valdivia et al, 1988) and has also been shown to block the delayed rectifier current in squid axon (Carbone et al, 1982(Carbone et al, , 1987.…”
Section: Discussionmentioning
confidence: 99%
“…Further analogies to channels in animal tissues may be found as more polypeptide toxins are characterized to be highly specific inhibitors of various K + channels (see recent work by Carbone et al, 1982Carbone et al, , 1987Lucero & Pappone, 1987). The possibility that these toxins could be used to help isolate the proteins could clearly lead to great advances in the study of these channel proteins.…”
Section: Discussionmentioning
confidence: 99%